Analisis tata kelola pembiayaan usahatani jagung di kabupaten Pasaman Barat - Afdal Afdal; Endry Martius; Erwin Erwin (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
This study aims to describe the management pattern of corn farming financing in West Pasaman Regency and analyze problems in the management of corn farming financing in West Pasaman Regency and analyze factors related to the financing management of corn farming activities in West Pasaman Regency. The study used a simple random sampling method with a survey design. Data were collected by in-depth interviews with 8 key informants, and respondents with a questionnaire of 125 samples. Data analysis was carried out using a qualitative descriptive method to describe the pattern of financing management for corn farming activities, and analyze problems in the management of corn farming financing and quantitative analysis to analyze factors related to the management of corn farming financing in West Pasaman Regency by coding. (1, 2, 3 and 4) to all statements in the questionnaire. The results showed that there were 3 (toga) patterns of sources of financing for corn farming in West Pasaman Regency, including: 1) self-financing patterns of 57.6%, 2) private financing patterns of 40.0%, and 3) government financing patterns of 57.6%. 2.4%. The use of the pattern of sources of financing for corn farming by farmers is equally good, but the pattern of self-financing tends to be more in demand by farmers, while the pattern of private and government financing is only of interest to certain farmers. The three patterns of financing corn farming, both independent, private and government patterns did not find significant problems for farmers in corn farming, either individually or in partnership. There is a strong relationship between the characteristics of farmers and sources of financing, and a strong relationship between the characteristics of farmers and farming activities at the production activity stage as well as a strong relationship between the source of financing and the stages of business activities contained in the activity and post-production stages.